Facilitating Mathematical Creative Thinking Ability: Analysis of Validation, Practicality, and Effectiveness of Learning Modules - Solfitri, Titi; Siregar, Hesty Marwani; Kartini, Kartini; Permata, Ariya (Jurnal Pendidikan Progresif, 2024)
Abstract: Facilitating Mathematical Creative Thinking Ability: Analysis of Validation and Student Response to Learning Modules. Objective: This study aims to determine the validity and practicality of the developed module of integration technique in integral calculus learning; and to find out whether the module of integration technique in integral calculus learning developed is effective in improving students' mathematical creative thinking ability. Methods: The module was developed using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Two experts conducted the validation, resulting in an average validity score of 3.67, categorized as very valid. The practicality of the module was assessed through a student response questionnaire, which resulted in an average practicality percentage of 81%, classified as very practical. The effectiveness of the module was evaluated by comparing students' pretest and posttest scores on mathematical creative thinking skills. Findings: The analysis showed a significant improvement in students' scores, with the average score increasing from 1.13 in the pretest to 5.06 in the posttest. The average n-gain was calculated at 0.59, which falls into the moderate category. These results indicate that the module is effective in enhancing students' mathematical creative thinking skills. Conclusion: The study concludes that the developed learning module effectively improves students' mathematical creative thinking skills and can be utilized as a teaching material in integral calculus courses. The development of this module has significant implications for enhancing the quality of mathematics education in the digital era. Keywords: mathematical creative thinking, integral calculus, ADDIE model, integration technique.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202445